Effects of outdoor recreation on wildlife in protected areas - Larson, Courtney Louise, author; Crooks, Kevin R., advisor; Reed, Sarah E., advisor; Bailey, Larissa L., committee member; Knight, Richard L., committee member (Colorado State University. Libraries, 2019)
Biodiversity is undergoing dramatic declines worldwide. Protected areas are the primary strategy used to conserve biodiversity, but they are rarely completely free from threats that imperil ecological communities. The vast majority of protected areas are open to recreation and have a dual mission to conserve natural resources while providing access for outdoor recreation. Many protected areas receive high levels of recreational use, particularly those near large human populations. An increasing body of evidence shows that recreation can have negative effects on animals, but questions remain about the frequency, consistency, and magnitude of the effects of recreation. To address these knowledge gaps, I conducted a global meta-analysis of the effects of recreation on vertebrate richness and abundance. I reviewed and extracted data from 34 articles that compared vertebrate richness and abundance at sites with low and high levels of recreational use, and estimated that vertebrate richness and abundance are lower in association with higher levels of recreation in over two-thirds (70%) of cases. I observed a moderate negative group-level effect of recreation on bird and mammal abundance, but the group-level effect on fish and reptiles was not significant. Effects were stronger for carnivores and herbivores than for omnivores, and stronger for small-bodied birds and ground-nesting birds than larger and tree- and shrub-nesting birds. Terrestrial and non-motorized activities were associated with reduced vertebrate abundance, whereas aquatic and motorized activities were not. While categorical comparisons between low and high levels of use can help establish whether recreation effects exist, managers who must plan and regulate recreational use of protected areas need to understand the levels of human activity that trigger animal responses. I assessed shifts in mammal habitat use and relative activity over a broad gradient of human activity levels at 92 sampling points located in 14 nature reserves in San Diego County, California, USA. I used camera traps to measure both human and mammal use of reserves, and I modeled mammal habitat use (occupancy and detection probability) and relative activity rates (hours per day with detections) in association with daily counts of total human activity, pedestrians, and cyclists. Human activity was associated with declines in habitat use of several mammal species, particularly bobcats and mule deer, though the strength of these effects was less than the effects of covariates characterizing habitat, topography, and development. Although human activity may not often extirpate mammal species from urban habitat fragments, it can reduce habitat suitability. In particular, bobcat, gray fox, mule deer, and raccoon were less active in areas with higher levels of human activity. Recreation has negative consequences for many animal species, but its effects on reptiles are largely unknown. I evaluated the effects of non-motorized, non-consumptive recreation on reptiles within urban protected areas in a fragmented landscape in coastal southern California, USA. I surveyed for lizards and snakes, quantified human activity, and modeled species richness, community composition, and occupancy as a factor of human activity along with other variables known to affect reptile distributions. I observed a decline in species richness in association with human activity, which was driven primarily by a decrease in lizard richness. The proportion of specialist species was not affected by human activity. Human activity was associated with a decline in occupancy of the common side-blotched lizard (Uta stansburiana), a slight but uncertain decline in occupancy of the orange-throated whiptail (Aspidoscelis hyperythra) and no relationship with western fence lizard (Sceloporus occidentalis) occupancy. Our study demonstrates that human activity can reduce the ability of urban protected areas to conserve diverse reptile communities. My study demonstrates the importance of examining the effects of recreation across a wide gradient of human activity and across a broad suite of species to understand which species are sensitive to recreation, to what thresholds of disturbance they respond, and whether their response results in reduced activity, local extirpation, lower species richness, or a change in community composition. These results pose a challenge to natural resource management agencies who must balance recreation access with natural resource protection, and to conservation organizations that rely on outdoor recreation for public support and funding. I recommend that managers plan recreational access at a regional scale and include some areas that are closed to recreation to minimize trade-offs between recreation and species conservation.
Keywords: protected area; wildlife; recreation; conservation